10(x+4)-4(x-2)=3(x-1)-2(3-x)

Simple and best practice solution for 10(x+4)-4(x-2)=3(x-1)-2(3-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(x+4)-4(x-2)=3(x-1)-2(3-x) equation:



10(x+4)-4(x-2)=3(x-1)-2(3-x)
We move all terms to the left:
10(x+4)-4(x-2)-(3(x-1)-2(3-x))=0
We add all the numbers together, and all the variables
10(x+4)-4(x-2)-(3(x-1)-2(-1x+3))=0
We multiply parentheses
10x-4x-(3(x-1)-2(-1x+3))+40+8=0
We calculate terms in parentheses: -(3(x-1)-2(-1x+3)), so:
3(x-1)-2(-1x+3)
We multiply parentheses
3x+2x-3-6
We add all the numbers together, and all the variables
5x-9
Back to the equation:
-(5x-9)
We add all the numbers together, and all the variables
6x-(5x-9)+48=0
We get rid of parentheses
6x-5x+9+48=0
We add all the numbers together, and all the variables
x+57=0
We move all terms containing x to the left, all other terms to the right
x=-57

See similar equations:

| 5t+6=11 | | 3(x-8)-6=-6(-3x+7)-6x | | 5x+5-2x=14 | | 6=6m-4m | | 7x+17=4(x+2) | | 2x+1+6x=-15 | | 3(u-5)=3u+3 | | 4(3x+2)=4(2x+3)+4x= | | 15x-3=10x+60 | | 4t-17t=39 | | 17+13-6x= | | -5x+3(x-7)=-19 | | 10z–5=5z | | 9x^2−25=30x−50 | | -48=5y+2 | | 5g+7=7+5g | | -8(2n+9)=10n | | x2+18X+9=0 | | −5x+3(x-7)=−19 | | x(x-11)=3 | | P(x)=x^2+10 | | 7y+5=23 | | -1y=6 | | 7+3(2g+6)=-29 | | -4=3m-16 | | 4=(y+10)/2 | | 2t+8=–4(t+1) | | -3-7(1+6d)=28 | | -1/5(w-1)=15 | | -19w=2w+9-6w | | 4x=19-(-17) | | -15+16=86-29p |

Equations solver categories